1997
DOI: 10.1002/(sici)1099-0488(199710)35:14<2363::aid-polb14>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structure and properties of a liquid crystalline epoxy during curing

Abstract: The evolution of structure, and thermal and dynamic mechanical properties of a liquid crystalline epoxy during curing has been studied with differential scanning calorimetry (DSC), polarized optical microscopy, x‐ray scattering, and dynamic mechanical analysis. The liquid crystalline epoxy was the diglycidyl ether of 4,4′‐dihydroxy‐α‐methylstilbene (DGEDHMS). Two curing agents were used in this study: a di‐functional amine, the aniline adduct of DGEDHMS, and a tetra‐functional sulfonamido amine, sulfanilamide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 1 publication
4
31
0
Order By: Relevance
“…Gelation is thereby independent of liquid crystalline phase as well as cure temperature. In other studies it has been generally found that reaction kinetics is enhanced in more ordered phases (Guymon and Bowman, 1997;Liu et al, 1997;Mormann and Brocher, 1999) and that the network formation tends to stabilize more ordered phases (Lin et al, 1997;Shiota and Ober, 1997). However, there are also examples in which the network formation destabilizes the liquid crystalline phase (Gavrin and Douglas, 2001;Osada et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
“…Gelation is thereby independent of liquid crystalline phase as well as cure temperature. In other studies it has been generally found that reaction kinetics is enhanced in more ordered phases (Guymon and Bowman, 1997;Liu et al, 1997;Mormann and Brocher, 1999) and that the network formation tends to stabilize more ordered phases (Lin et al, 1997;Shiota and Ober, 1997). However, there are also examples in which the network formation destabilizes the liquid crystalline phase (Gavrin and Douglas, 2001;Osada et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
“…Robinson et al [7] studied curing of the same epoxy monomer, DOMS, with methylene dianiline (MDA), SAA, and BSA and showed that curing is accompanied by a phase transition. Lin et al [8] examined the evolution of the LC structure and the thermal properties in the systems DOMS-SAA and DOMS-aniline adduct with DOMS. The aforementioned studies use a LC monomer (DOMS), which develops the monotropic LC phase on cooling.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the overall curing reaction kinetics is strongly affected by the presence of a LC phase. E. Amendola, [7] J. P. Liu, [8] Q. G. Lin [9] and A. A. Robinson [10] et al studied the curing reaction of the diglycidyl ether of 4,49-dihydroxy-a-methylstilbene with amine, and found an unusual exothermic double peak and that birefringent textures were developed during isothermal cure as the reaction proceeded.…”
Section: Introductionmentioning
confidence: 99%